Performance of hollow reinforced concrete beam in structural member / Hamidun Mohd Noh...[et al.] - Mohd Noh, Hamidun; Mohamad, Nor Lailatul Izzatil Azwani; Bangau, Rolly (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Recently, the problem faced by the construction industry is a significant shortage of raw materials of concrete. Thus, the main idea of this research is to replace the use of concrete at the middle area of neutral axis of beam with voided system by incorporating PVC pipe. This research aims to reduce the concrete usage; structure's self-weight without neglecting its strength performance. The experimental work consists of casting and testing the 1200 x 160 x 160 mm beams with (Ø40 mm, Ø50 mm, and Ø100 mm) and without void at the neutral axis. The test results indicated that the strength performance of all RC beams with voided section is stronger than the ordinary RC beam where the V50 RC beam is able to withstand loads up to 38.25 kN and has a strength increment of 49.2% compared to the ordinary RC beam. By this material optimization, the reduction of concrete usage and self-weight of the V100 RC beam recorded a reduction of up to 35.14% but in terms of its strength is relatively low compared to the V40 RC beam and V50 RC beam. This findings show a positive result in reducing the dead load without affecting the strength of the structure. Besides aiming to the reduction of concrete usage and structure's self-weight, the idea of this research could be used and implemented in producing a lightweight structure with easy handling and installing, and at the same time focusing to meet the IBS system.